The wise advisor : what every professional should know about consulting and counseling - Salacuse, Jeswald W. (Praeger, 2000)
This work provides practical advice on the process of counselling and consulting. Salacuse's system is based on basic principles that govern all advising, regardless of profession: know the client; recognize how advice matters; develop a partnership; and tailor advice to the client's needs.